2022
DOI: 10.1007/s00429-022-02490-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of the default mode network in longitudinal functional brain reorganization of brain gliomas

Abstract: The study of patients after glioma resection offers a unique opportunity to investigate brain reorganization. It is currently unknown how the whole-brain connectomic profile evolves longitudinally after surgical resection of a glioma and how this may be associated with tumor characteristics and cognitive outcome. In this longitudinal study, we investigate the impact of tumor lateralization and grade on functional connectivity (FC) in highly connected networks, or hubs, and cognitive performance. Twenty-eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…Our analysis of the relationship between cortical lesions and impairment in verbal fluency one week after surgery confirmed the involvement of the left superior frontal gyrus in phonemic fluency and of the left superior temporal gyrus in semantic fluency, in accordance with previous results that identified a cortical dissociation ( Baldo et al, 2006 , Billingsley et al, 2004 , Henry and Crawford, 2004 , Hirshorn and Thompson-Schill, 2006 , Schmidt et al, 2019 ). Interestingly, in the FU assessment no negative relationships were found between cortical lesions and fluencies: this result reinforces the idea of a functional reorganization, thanks to the cortical plasticity, that may occur after glioma resection, in particular for motor function and language ( Cirillo et al, 2019 , Conway et al, 2017 , Duffau, 2020 , Duffau, 2021 , Duffau, 2020 , Duffau, 2014 , Duffau et al, 2003 , Saviola et al, 2022 ). Indeed, cortical areas nearby the tumor may have plastically reorganized their functions, in order to compensate the brain lesion ( Duffau, 2020 , Duffau, 2021 , Duffau, 2014 , Duffau et al, 2003 ).…”
Section: Discussionsupporting
confidence: 77%
“…Our analysis of the relationship between cortical lesions and impairment in verbal fluency one week after surgery confirmed the involvement of the left superior frontal gyrus in phonemic fluency and of the left superior temporal gyrus in semantic fluency, in accordance with previous results that identified a cortical dissociation ( Baldo et al, 2006 , Billingsley et al, 2004 , Henry and Crawford, 2004 , Hirshorn and Thompson-Schill, 2006 , Schmidt et al, 2019 ). Interestingly, in the FU assessment no negative relationships were found between cortical lesions and fluencies: this result reinforces the idea of a functional reorganization, thanks to the cortical plasticity, that may occur after glioma resection, in particular for motor function and language ( Cirillo et al, 2019 , Conway et al, 2017 , Duffau, 2020 , Duffau, 2021 , Duffau, 2020 , Duffau, 2014 , Duffau et al, 2003 , Saviola et al, 2022 ). Indeed, cortical areas nearby the tumor may have plastically reorganized their functions, in order to compensate the brain lesion ( Duffau, 2020 , Duffau, 2021 , Duffau, 2014 , Duffau et al, 2003 ).…”
Section: Discussionsupporting
confidence: 77%
“…Our analysis of the relationship between cortical lesions and impairment in verbal fluency one week after surgery confirmed the involvement of the left superior frontal gyrus in phonemic fluency and of the left superior temporal gyrus in semantic fluency, in accordance with previous results that identified a cortical dissociation (Baldo et al, 2006;Billingsley et al, 2004;Henry and Crawford, 2004;Hirshorn and Thompson-Schill, 2006;Schmidt et al, 2019). Interestingly, in the FU assessment no negative relationships were found between cortical lesions and fluencies: this result reinforces the idea of a functional reorganization, thanks to the cortical plasticity, that may occur after glioma resection, in particular for motor function and language (Cirillo et al, 2019;Conway et al, 2017;Duffau, 2021;Duffau, 2020;Duffau, 2014;Duffau et al, 2003;Saviola et al, 2022). Indeed, cortical areas nearby the tumor may have plastically reorganized their functions, in order to compensate the brain lesion (Duffau, 2021;Duffau, 2014;Duffau et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, PCC was regarded as the hub of the default mode network (DMN), participating in the initial deactivated function and in engaging in spontaneous cognition ( 25 ). A recent imaging study on brain glioma showed that neurological profiles, including verbal fluency, verbal memory, and visual memory, are longitudinally associated with spatial features of the connectome, which is mainly within the DMN ( 26 ). Another study found that the surgical tissue changes of brain glioma, such as resection cavities or edema, have strong negative impacts on DMN nodes that result in bad performance in language processing and verbal working memory ( 27 ).…”
Section: Discussionmentioning
confidence: 99%